Skip to content

Higher Order Derivatives

Higher-Order Derivatives: Rigorous Definition and Notation

If a function \( y = f(x) \) is differentiable, we can compute its first derivative \( f'(x) \) or \( \frac{dy}{dx} \), which represents the rate of change of \( y \) with respect to \( x \). If this derivative itself is differentiable, we can differentiate it again to obtain the second derivative, and this process can be continued to define derivatives of higher order.

Second-Order Derivative

The second derivative is defined as the derivative of the first derivative:

\[ \frac{d}{dx} \left( \frac{dy}{dx} \right) = \frac{d^2y}{dx^2} \]

or equivalently, in function notation:

\[ \frac{d}{dx} \left( f'(x) \right) = f''(x) \]

This represents the rate of change of the first derivative, which provides information about the curvature or concavity of the function (we will learn later the correct interpretation).

Third-Order Derivative

If the second derivative exists and is differentiable, we can differentiate it again:

\[ \frac{d}{dx} \left( \frac{d^2y}{dx^2} \right) = \frac{d^3y}{dx^3} \]

or in function notation:

\[ \frac{d}{dx} \left( f''(x) \right) = f'''(x) \]

\( n \)th-Order Derivative

Proceeding inductively, if the \((n-1)\)th derivative exists and is differentiable, then the \( n \)th-order derivative is defined as:

\[ \frac{d}{dx} \left( \frac{d^{n-1}y}{dx^{n-1}} \right) = \frac{d^n y}{dx^n} \]

or, equivalently,

\[ \frac{d}{dx} \left( f^{(n-1)}(x) \right) = f^{(n)}(x) \]

where \( f^{(n)}(x) \) represents the \( n \)th derivative of \( f(x) \).

Thus, the process of differentiation can be iterated indefinitely, provided that the required derivatives exist. The notation follows a structured pattern:

  • For small values of \( n \):

    \[ f'(x), \quad f''(x), \quad f'''(x) \]
  • For \( n \geq 4 \), parentheses are used:

    \[ f^{(4)}(x), \quad f^{(5)}(x), \quad \dots, \quad f^{(n)}(x) \]
  • In Leibniz notation, the general form is:

    \[ \frac{d^n y}{dx^n} \]

which emphasizes that the differentiation operator \( \frac{d}{dx} \) is applied \( n \) times.

nth order derivatives of some common functions

Let us now calculate the \( n \)th-order derivatives of some common functions by differentiating repeatedly and then generalizing the pattern using induction.


1. Power Function: \( f(x) = x^m \)

We begin with a power function \( f(x) = x^m \), where \( m \) is any real number. The first derivative is:

\[ f'(x) = m x^{m-1}. \]

Differentiating again,

\[ f''(x) = m (m-1) x^{m-2}. \]

Continuing this process, we observe the pattern:

\[ f^{(n)}(x) = m (m-1) (m-2) \dots (m-n+1) x^{m-n}. \]

Using factorial notation, we write:

\[ f^{(n)}(x) = \frac{m!}{(m-n)!} x^{m-n}, \quad \text{for } m \geq n. \]

For \( n > m \), the derivative vanishes:

\[ f^{(n)}(x) = 0, \quad \text{for } n > m. \]

2. Exponential Function: \( f(x) = e^x \)

The function \( e^x \) is unique in that differentiating it any number of times gives the same function:

\[ f'(x) = e^x, \quad f''(x) = e^x, \quad f'''(x) = e^x, \quad \dots \]

Thus, for any \( n \geq 1 \),

\[ f^{(n)}(x) = e^x. \]

3. General Exponential Function: \( f(x) = a^x \)

For a constant base \( a > 0 \), the first derivative is:

\[ f'(x) = (\ln a) a^x. \]

Differentiating again,

\[ f''(x) = (\ln a)^2 a^x. \]

By induction, the \( n \)th derivative follows as:

\[ f^{(n)}(x) = (\ln a)^n a^x. \]

4. Reciprocal Function: \( f(x) = \frac{1}{x} \)

Rewriting as \( f(x) = x^{-1} \), the first derivative is:

\[ f'(x) = -x^{-2} = -\frac{1}{x^2}. \]

Differentiating again,

\[ f''(x) = 2 x^{-3} = \frac{2}{x^3}. \]

Proceeding inductively, we obtain:

\[ f^{(n)}(x) = (-1)^n \frac{n!}{x^{n+1}}, \quad n \geq 1. \]

5. Reciprocal of a Linear Function: \( f(x) = \frac{1}{ax+b} \)

Using the chain rule, the first derivative is:

\[ f'(x) = -\frac{a}{(ax+b)^2}. \]

Differentiating again,

\[ f''(x) = \frac{2a^2}{(ax+b)^3}. \]

Observing the pattern, we generalize:

\[ f^{(n)}(x) = (-1)^n \frac{n! a^n}{(ax+b)^{n+1}}, \quad n \geq 1. \]

6. Sine Function: \( f(x) = \sin x \)

The derivatives of \( \sin x \) follow a cyclic pattern:

\[ f'(x) = \cos x, \quad f''(x) = -\sin x, \quad f'''(x) = -\cos x, \quad f^{(4)}(x) = \sin x. \]

Extending this to the \( n \)th derivative, we observe:

\[ f^{(n)}(x) = \sin \left( x + n \frac{\pi}{2} \right). \]

7. Cosine Function: \( f(x) = \cos x \)

Similar to the sine function, the derivatives of \( \cos x \) repeat every four steps:

\[ f'(x) = -\sin x, \quad f''(x) = -\cos x, \quad f'''(x) = \sin x, \quad f^{(4)}(x) = \cos x. \]

Thus, the general formula for the \( n \)th derivative is:

\[ f^{(n)}(x) = \cos \left( x + n \frac{\pi}{2} \right). \]

8. Product Function: \( f(x) = x e^x \)

We now compute the \( n \)th derivative of \( f(x) = x e^x \). Using the product rule:

\[ f'(x) = (x+1)e^x. \]

Differentiating again,

\[ f''(x) = (x+2)e^x. \]

Repeating this process, we obtain the general form:

\[ f^{(n)}(x) = (x+n) e^x. \]

Summary of Results

Function \( n \)th Derivative
\( x^m \) \( \frac{m!}{(m-n)!} x^{m-n}, \quad n \leq m \); 0 otherwise
\( e^x \) \( e^x \)
\( a^x \) \( (\ln a)^n a^x \)
\( \frac{1}{x} \) \( (-1)^n \frac{n!}{x^{n+1}} \)
\( \frac{1}{ax+b} \) \( (-1)^n \frac{n! a^n}{(ax+b)^{n+1}} \)
\( \sin x \) \( \sin \left( x + n \frac{\pi}{2} \right) \)
\( \cos x \) \( \cos \left( x + n \frac{\pi}{2} \right) \)
\( x e^x \) \( (x+n) e^x \)

These formulas illustrate how different types of functions exhibit distinct patterns in their higher-order derivatives. Understanding these patterns allows for efficient computation of derivatives in various mathematical contexts.

Leibniz Rule for product of two fucntions

Let us compute the derivatives of a product of two differentiable functions \( f(x) \) and \( g(x) \) systematically, starting with the first few derivatives and then generalizing to the \( n \)th-order case.

First Derivative (Standard Product Rule)

Applying the product rule:

\[ \frac{d}{dx} [f(x) g(x)] = f'(x) g(x) + f(x) g'(x). \]

This formula states that the derivative of a product is the sum of two terms: one where we differentiate \( f(x) \) while keeping \( g(x) \) fixed, and another where we differentiate \( g(x) \) while keeping \( f(x) \) fixed.


Second Derivative

Differentiating both sides again:

\[ \frac{d^2}{dx^2} [f(x) g(x)] = \frac{d}{dx} \left[ f'(x) g(x) + f(x) g'(x) \right]. \]

Applying the product rule to each term:

\[ = f''(x) g(x) + f'(x) g'(x) + f'(x) g'(x) + f(x) g''(x). \]

Rearranging,

\[ \frac{d^2}{dx^2} [f(x) g(x)] = f''(x) g(x) + 2 f'(x) g'(x) + f(x) g''(x). \]

Notice that the coefficient 2 appears in front of the middle term.


Third Derivative

Differentiating again:

\[ \frac{d^3}{dx^3} [f(x) g(x)] = \frac{d}{dx} \left[ f''(x) g(x) + 2 f'(x) g'(x) + f(x) g''(x) \right]. \]

Applying the product rule to each term:

\[ = f'''(x) g(x) + f''(x) g'(x) + 2 f''(x) g'(x) + 2 f'(x) g''(x) + f'(x) g''(x) + f(x) g'''(x). \]

Rearranging,

\[ \frac{d^3}{dx^3} [f(x) g(x)] = f'''(x) g(x) + 3 f''(x) g'(x) + 3 f'(x) g''(x) + f(x) g'''(x). \]

The coefficients 1, 3, 3, 1 are exactly the third row of Pascal’s triangle (binomial coefficients).


Pattern and Generalization

Observing the derivatives, we notice the general structure:

\[ \frac{d^n}{dx^n} [f(x) g(x)] = \sum_{k=0}^{n} \binom{n}{k} f^{(k)}(x) g^{(n-k)}(x). \]

where \( \binom{n}{k} \) is the binomial coefficient:

\[ \binom{n}{k} = \frac{n!}{k!(n-k)!}. \]

This follows by induction and generalizes the product rule to higher-order derivatives.

Thus, for any order \( n \), the derivative of a product follows the structure of expanding a binomial expression, where each term consists of a combination of derivatives of \( f(x) \) and \( g(x) \) multiplied by the corresponding binomial coefficient. COnsider the following example:

Let \( f(x) = x^2 \) and \( g(x) = e^x \). We compute \( \frac{d^3}{dx^3} (x^2 e^x) \):

Applying Leibniz's rule:

\[ \frac{d^3}{dx^3} (x^2 e^x) = \sum_{k=0}^{3} \binom{3}{k} f^{(k)}(x) g^{(3-k)}(x). \]

Computing individual terms:

  • \( f(x) = x^2 \Rightarrow f^{(0)}(x) = x^2, \quad f^{(1)}(x) = 2x, \quad f^{(2)}(x) = 2, \quad f^{(3)}(x) = 0 \).
  • \( g(x) = e^x \Rightarrow g^{(n)}(x) = e^x \) for all \( n \).

Substituting:

\[ \frac{d^3}{dx^3} (x^2 e^x) = \binom{3}{0} x^2 e^x + \binom{3}{1} 2x e^x + \binom{3}{2} 2 e^x + \binom{3}{3} 0. \]

Simplifying:

\[ (x^2 + 6x + 6) e^x. \]

Double Derivative of Inverse of a Function

Let \( f \) be an invertible function, and let \( g \) be its inverse, so that \( g(x) = f^{-1}(x) \). We already know that the first derivative of \( g(x) \) is given by

\[ g'(x) = \frac{1}{f'(g(x))}. \]

Differentiating both sides again,

\[ g''(x) = \frac{d}{dx} \left( \frac{1}{f'(g(x))} \right). \]

Applying the chain rule,

\[ g''(x) = -\frac{1}{[f'(g(x))]^2} \cdot \frac{d}{dx} [f'(g(x))]. \]

Since \( f'(g(x)) \) is a composite function, differentiating it gives

\[ \frac{d}{dx} [f'(g(x))] = f''(g(x)) g'(x). \]

Substituting this back,

\[ g''(x) = -\frac{1}{[f'(g(x))]^2} \cdot f''(g(x)) g'(x). \]

Using the previously known result \( g'(x) = \frac{1}{f'(g(x))} \), we substitute \( g'(x) \):

\[ \boxed{g''(x) = -\frac{f''(g(x))}{[f'(g(x))]^3}}. \]

This result expresses the second derivative of an inverse function purely in terms of the derivatives of \( f(x) \), evaluated at \( g(x) \).

Double Derivative of a Parametric Function

Let \( x = f(t) \) and \( y = g(t) \) be a parametrically defined function. We already know that the first derivative of \( y \) with respect to \( x \) is given by

\[ \frac{dy}{dx} = \frac{\frac{dy}{dt}}{\frac{dx}{dt}} = \frac{g'(t)}{f'(t)}. \]

Differentiating this again with respect to \( x \),

\[ \frac{d^2y}{dx^2} = \frac{d}{dx} \left( \frac{g'(t)}{f'(t)} \right). \]

Since \( t \) is an implicit function of \( x \), we use the chain rule,

\[ \frac{d^2y}{dx^2} = \frac{d}{dt} \left( \frac{g'(t)}{f'(t)} \right) \frac{dt}{dx}. \]

Applying the quotient rule to differentiate \( \frac{g'(t)}{f'(t)} \),

\[ \frac{d}{dt} \left( \frac{g'(t)}{f'(t)} \right) = \frac{f'(t) g''(t) - g'(t) f''(t)}{[f'(t)]^2}. \]

Since \( \frac{dt}{dx} = \frac{1}{dx/dt} = \frac{1}{f'(t)} \), substituting this,

\[ \frac{d^2y}{dx^2} = \frac{f'(t) g''(t) - g'(t) f''(t)}{[f'(t)]^2} \cdot \frac{1}{f'(t)}. \]

Simplifying,

\[ \frac{d^2y}{dx^2} = \frac{f'(t) g''(t) - g'(t) f''(t)}{[f'(t)]^3}. \]

This expresses the second derivative of a parametrically defined function in terms of the first and second derivatives of \( f(t) \) and \( g(t) \).